MANAGEMENT OF PRE-CANCEROUS LESION BY TURMERIC- AN OVERVIEW - *Nidhi Singh; T.P.Chaturvedi; H.C.Baranwal (International Journal of Ayurveda and Pharma Research, 2019)
Turmeric, “The Indian golden spice” is used since ancient times as therapeutic measure to cure disease and beauty enhancement. There are a variety of ways to use turmeric in dentistry, such as plaque detection system, pit and fissure sealant, intracanal medicament and subgingival irrigant, amongst which using it as a therapy for pre-cancerous lesion would be a pioneer in treatment modality. Pre-cancerous lesions can transform cancer, if not treated timely. Oral health being a crucial part of systemic health can be enhanced to many folds by using various parts of this medicinal plant. Present paper aims to enlighten the use of turmeric in various precancerous lesions because of its inherent property as anti-inflammatory, antioxidative and antineoplastic effects. It is simple to use and acceptable due to its taste and zero side effects. It is cost effective; hence make this herbal medicine an easy choice for patients and helps them to cure from precancerous lesions such as oral submucous fibrosis, oral lichen planus, oral leukoplakia and other tobacco-associated lesions also.